2000
DOI: 10.1029/2000jd900100
|View full text |Cite
|
Sign up to set email alerts
|

Simulating convective events using a high‐resolution mesoscale model

Abstract: Abstract. Four multiscale numerical simulations of convective events are analyzed to determine the essential characteristics of a numerical model which lead to useful simulations of convective events. Although several universities and weather forecasting centers are currently running high-resolution forecast models, the predictability of convective events, especially in the warm season, is still an issue among researchers and forecasters in the meteorological community. This study shows that explicit simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…Tucker and Crook, 1998;Romero et al 1998;Bernardet et al 2000;Zhang et al 2003 and many others). However, there is still a lot of room for improvement in simulating these convective systems.…”
Section: Discussion Of Modelling Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Tucker and Crook, 1998;Romero et al 1998;Bernardet et al 2000;Zhang et al 2003 and many others). However, there is still a lot of room for improvement in simulating these convective systems.…”
Section: Discussion Of Modelling Resultsmentioning
confidence: 97%
“…Pan et al 2004). Bernardet et al (2000) suggest that the sensitivity of the convective The role that topography plays in extreme precipitating events in South Africa has been identified in numerous studies. Laing and Fritsch,(l993b) found that the eastern escarpment plays an important role in the development of MCCs in the region, which is common initiating mechanism for these types of systems around the world (Laing and Fritsch, 1997).…”
Section: Backward Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our expectation that this will improve the ROC is motivated by the observation that location errors dominate precipitation forecast errors when compared to errors in forecasted volume and pattern (Ebert and McBride, 2000). Simulated convective storm are often a few hours off, or a few tens of kilometres away from the observed one (Bernardet et al, 2000).…”
Section: Neighbourhood Inclusion Methodsmentioning
confidence: 99%
“…Various studies done by Cardoso et al (2012) and Heikkila et al (2011) showed that high-resolution simulations are required especially for complex terrain, despite the high computational costs of such simulations. Adlerman and Droegemeier (2002) and Bernadet et al (2000) indicated that some processes such as strong convection can only be captured when the resolution of the numerical model is decreased below 2 km. Evaluations done over extended periods of time (Nachamkin and Hodur, 2000) have proven that increasing the horizontal resolution of weather prediction models improves numerical forecasts especially for integration domains with complex topographic features.…”
Section: Introductionmentioning
confidence: 99%